Consumers of different generations towards innovative technologies in customer service in retail - Kucharska, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The aim of the paper is to identify the importance of innovative technologies used in retail during the pandemic for consumers and the willingness of different generations of consumers to use these solutions in the future. The article was prepared on the basis of the literature on the subject, research reports, websites of companies preparing or implementing modern technologies in retail, and the results of direct research conducted in 2022 using the online survey technique among 1,100 consumers. The paper presents the issues related to the possibility of using modern technologies in the customer service process, specifically those that allow for even greater customer involvement in the purchasing process and increase their independence and self-service. A special emphasis was given to the self-service store, currently considered one of the greatest achievements (“milestones”) in brick-and-mortar retail trade, which is crucial for the issues presented. The paper shows the results of direct research on selected elements of purchasing behavior of different generations of consumers that are related to the use of innovative solutions in retail trade and intentions to use these solutions in the future.
Keywords: modern technology; customer service; retail; consumer generation